2020
DOI: 10.3390/ijms21114189
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between IL-8 Circulating Levels and TLR2 Hepatic Expression in Women with Morbid Obesity and Nonalcoholic Steatohepatitis

Abstract: The progression of nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis (NASH) is linked to systemic inflammation. Currently, two of the aspects that need further investigation are diagnosis and treatment of NASH. In this sense, the aim of this study was to assess the relationship between circulating levels of cytokines, hepatic expression of toll-like receptors (TLRs), and degrees of NAFLD, and to investigate whether these levels could serve as noninvasive biomarkers of NASH. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 69 publications
1
39
0
1
Order By: Relevance
“…The NAFLD progression mechanism is usually explained with the “multiple hit” theory of NAFLD pathogenesis, which states that lipid accumulation triggers liver steatosis, bringing about other processes such as adipokine release, inflammation, lipotoxicity, glucose, and lipid homeostasis dysregulation, which end up causing non-alcoholic steatohepatitis (NASH) and cirrhosis. Systemic inflammation is linked to progression to NASH, but it is also related to other pathological processes, such as innate immunity alterations, oxidative stress, mitochondrial dysfunction, toll-like receptors activation, and gut dysbiosis [ 7 ]. In this sense, the gut–liver axis plays a key role in the progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…The NAFLD progression mechanism is usually explained with the “multiple hit” theory of NAFLD pathogenesis, which states that lipid accumulation triggers liver steatosis, bringing about other processes such as adipokine release, inflammation, lipotoxicity, glucose, and lipid homeostasis dysregulation, which end up causing non-alcoholic steatohepatitis (NASH) and cirrhosis. Systemic inflammation is linked to progression to NASH, but it is also related to other pathological processes, such as innate immunity alterations, oxidative stress, mitochondrial dysfunction, toll-like receptors activation, and gut dysbiosis [ 7 ]. In this sense, the gut–liver axis plays a key role in the progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation associated with sustained TNF‐α and IL‐8 release ultimately leads to the accumulation of extracellular matrix and the development of fibrosis. ( 52 ) A recent clinical study of patients with biopsy‐proven NAFLD identified higher plasma TNF‐α and IL‐8 levels as biomarkers of significant fibrosis (versus mild/no fibrosis). ( 55 ) These data suggest that circulating levels of both TNF‐α and IL‐8 may be directly related to NAFLD progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-8 levels can identify the presence of significant fibrosis in NASH patients ( 68 ), and are elevated in NAFLD patients when compared to both obese and non-obese controls ( 61 ). Additionally, a positive correlation between circulating IL-8 levels and the histological NASH parameters, lobular inflammation and hepatocellular ballooning, was observed in NASH patients suffering from (morbid) obesity ( 68 , 69 ). The importance of IL-8 as diagnostic tool is further demonstrated by the possibility to, as only parameter in a panel of 24 analysed cytokines, significantly correlate with hepatic fibrosis after controlling for age, sex, BMI, hypertension, metabolic syndrome, and diabetes mellitus ( 67 ).…”
Section: Inflammatory Markersmentioning
confidence: 94%